An organometallic structure-activity relationship study reveals the essential role of a Re(CO)3 moiety in the activity against gram-positive pathogens including MRSA. Issue 1 (13th October 2014) - Patra, Malay; Wenzel, Michaela; Prochnow, Pascal; Pierroz, Vanessa; Gasser, Gilles; Bandow, Julia E.; Metzler-Nolte, Nils
Abstract : A systematic structure activity relationship reveals the contribution of individual organometallic moieties to the potency of a new structural class of hetero-trimetallic antibacterial agents. Abstract : The worrying appearance of microbial resistance to antibiotics is a worldwide problem which needs to be tackled urgently. Microbial resistance to the common classes of antibiotics involving purely organic compounds unfortunately develops very rapidly and in most cases, resistance was detected soon after or even before release of the antibiotic to the market. Therefore, novel concepts for antibiotics must be investigated, and metal-containing compounds hold particular promise in that area. Taking a trimetallic complex (1a ) which contains a ferrocenyl (Fc), a CpMn(CO)3 (cymantrene) and a [(dpa)Re(CO)3 ] residue as the lead structure, a systematic structure–activity relationship (SAR) study against various gram-positive pathogenic bacteria including methicillin-resistant Staphylococcus aureus (MRSA) strains was performed. The [(dpa)Re(CO)3 ] moiety was discovered to be the essential unit for the observed antibacterial activity of1a . The ferrocenyl and CpMn(CO)3 units can be replaced one by one or both together by organic moieties such as a phenyl ring without loss of antibacterial activity. The most potent mono-metallic complex (9c′ ) has an antibacterial activity comparable to the well-established organic drugs amoxicillin and norfloxacin and importantly, only moderate cytotoxicity against mammalian cells. Microbiological studies on membrane potential, membrane permeabilization, and cell wall integrity revealed that9c′ targets the bacterial membrane and disturbs cell wall integrity, but shows more efficient membrane permeabilization than the lead structure1a .